Association between relative fat mass and sterility in women of reproductive age in the United States: results from the 2013–2018 NHANES - Sun, Mengmeng; Lu, Yuxing; Yang, Xi; Mao, Xiaogang (Frontiers in Endocrinology, 2025)
BackgroundA major problem that affects women of reproductive age globally is sterility. A new statistic called Relative Fat Mass (RFM) provides an accurate representation of the percentage of total body fat in people. This study aims to investigate the relationship between RFM and sterility in fertility-age American women.MethodsThis study employed a cross-sectional design using data collected from NHANES between 2013 and 2018. The association between RFM and sterility was investigated using logistic regression analysis, controlling for a number of variables. The results were more resilient when RFM was transformed into a four-category variable in order to further examine the patterns of the association between different RFM levels and sterility. The dose-response association between RFM and sterility was illustrated using restricted cubic spline (RCS) analysis. Sensitivity and subgroup analyses were also conducted to assess the robustness and consistency of the results.ResultsThis study included 3,197 women aged 18–45, consisting of 2,854 non-sterile participants and 343 sterile participants. First, in the fully adjusted model, RFM and the prevalence of sterility had a positive correlation (OR = 1.05, 95% CI = 1.01–1.09). When converting RFM from a continuous to a categorical variable, the prevalence of sterility was significantly greater in the highest quartile than in the lowest quartile (OR = 2.59, 95% CI = 1.40–4.82). Furthermore, RFM and sterility prevalence were found to be positively linearly correlated by RCS analysis, with sterility rates sharply increasing as RFM levels rose. The positive correlation between RFM and the frequency of sterility was shown to be constant throughout various populations, according to subgroup analysis across stratified parameters. Finally, sensitivity analysis further confirmed the reliability and consistency of the study’s findings.ConclusionA representative sample of American women of reproductive age showed a positively correlation between RFM and the prevalence of sterility. RFM may help identify women at risk for sterility, and waist circumference management could potentially help lower the risk of sterility.